2015
DOI: 10.1111/acem.12714
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Ultrasonography in Retained Soft Tissue Foreign Bodies: A Systematic Review and Meta-analysis

Abstract: Objectives: Open wounds with the potential for retained foreign bodies are frequently seen in the emergency department (ED). Common foreign bodies, such as wood or glass, are often missed on physical examination and conventional radiography. The increased use of ultrasonography (US) in the ED presents an opportunity to better identify retained soft tissue foreign bodies, and understanding of its test characteristics is desirable. The authors set out to determine the test characteristics of US for detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 41 publications
0
40
0
3
Order By: Relevance
“…A recent systemic review concluded that US could be a powerful tool for the detection of FBs in the skin and soft tissues [10]. While Aras et al [1] investigated FBs with US using a single linear probe, Valizadeh et al [6] examined FBs with US using linear probes in different set-ups for different FBs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systemic review concluded that US could be a powerful tool for the detection of FBs in the skin and soft tissues [10]. While Aras et al [1] investigated FBs with US using a single linear probe, Valizadeh et al [6] examined FBs with US using linear probes in different set-ups for different FBs.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be unsuitable for those FBs which are in deep regions and inside the airfilled cavities [1,9]. In a recent study, Davis et al [10] published a systemic review and meta-analysis focused on the detection of FBs with US. They concluded that US could be a useful diagnostic tool in the evaluation of FBs located in the skin and soft tissues.…”
Section: Introductionmentioning
confidence: 99%
“…It is affordable and does not employ X ray beams and the obtained images are readily available for evaluation. However, this modality is not suitable for detection of objects in deep tissues or air filled cavities (14). …”
Section: Discussionmentioning
confidence: 99%
“…In one retrospective study of 200 patients Anderson et al showed that conventional radiographic studies identified wood foreign bodies only 15% of the time 4. Bray et al demonstrated that US has a sensitivity of 94% and specificity of 99% in the identification of STFBs.3 More recent studies, including a meta-analysis conducted by Davis et al showed that US has moderate sensitivity of 72% but still high specificity of 92% in the detection of STFBs 5. In addition, US can accurately measure the size of a lodged foreign body within ± 1 mm 3.…”
Section: Discussionmentioning
confidence: 99%